2019
DOI: 10.3389/fphar.2019.00169
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Optimized LC-MS Method for the Detection of Specialized Pro-Resolving Mediators in Biological Samples

Abstract: The cardioprotective and anti-inflammatory effects of long chain omega-3 polyunsaturated fatty acids (n3 PUFA) are believed to be partly mediated by their oxygenated metabolites (oxylipins). In the last two decades interest in a novel group of autacoids termed specialized pro-resolving mediators (SPMs) increased. These are actively involved in the resolution of inflammation. SPMs are multiple hydroxylated fatty acids including resolvins, maresins, and protectins derived from the n3 PUFA eicosapentaenoic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 74 publications
6
74
0
Order By: Relevance
“…In order to obtain the best results, they tried different compositions and gradients of the mobile phase [102]. Using a Zorbax Eclipse Plus C18 column with a diameter of particles less than 2 microns (150 × 2.1 mm, 1.8 µm; Agilent, Waldbronn, Germany) and an optimized gradient, Kutzner et al separated the maresin (Mar)1 and 7 (S)-Mar1 and protectin (N)PD1 and PDX stereoisomers from human serum and the results were comparable to those achieved by using a chiral column [103]. The high resolution power of approaches using these columns is usually used for separation of known isomers, not for identification of novel compounds.…”
Section: Chiral Chromatographymentioning
confidence: 88%
See 3 more Smart Citations
“…In order to obtain the best results, they tried different compositions and gradients of the mobile phase [102]. Using a Zorbax Eclipse Plus C18 column with a diameter of particles less than 2 microns (150 × 2.1 mm, 1.8 µm; Agilent, Waldbronn, Germany) and an optimized gradient, Kutzner et al separated the maresin (Mar)1 and 7 (S)-Mar1 and protectin (N)PD1 and PDX stereoisomers from human serum and the results were comparable to those achieved by using a chiral column [103]. The high resolution power of approaches using these columns is usually used for separation of known isomers, not for identification of novel compounds.…”
Section: Chiral Chromatographymentioning
confidence: 88%
“…Various parameters such as source temperature (ST), collision energy (CE), declustering potential (DP), collision cell exit potential (CEP), collision activated dissociation (CAD), and gas pressure affect the signal intensity in the SRM mode. Simultaneously, caution should be taken with increasing the temperature of nebulizer gas as well as auxiliary gas, because the optimum temperature for some compounds may lead to the thermal degradation of others [103]. To obtain better detection limits and avoid interference from nearby isomers, at the last step of optimization, the most intense and specific fragments and transitions are usually chosen [101,103,163].…”
Section: Lc-ms/msmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma concentrations of SAMPs, here SPM profiles, have also been measured using liquid chromatographytandem mass spectrometry (LC-MS) technology [49,50]. Of note, in a recently published evaluation of SPM profiles using an optimized LC-MS method for the detection of SPMs in biological samples, Kutzner et al [51] concluded, "SPMs were generally not detectable/quantifiable in plasma and serum of healthy individuals, while good recovery rates were found in spiked samples. These results strongly support findings that circulating levels of SPMs are very low, i.e., < 0.1 nM in healthy subjects.…”
Section: Plasma Concentration Of Hmgb1 S100 Proteins Circulating Dnmentioning
confidence: 99%